The relationship between workload and job satisfaction at North Butterworth Container Terminal, Penang Sdn. Bhd. / Nurmunirahizzati Yahya - Yahya, Nurmunirahizzati (2013)
The research was conducted to examine the relationship between workload and job satisfaction among employee. This research content two independent variable and one dependent variable. The independent variable are work-life balance and work stress and the dependent variable is job satisfaction. The research objective is to determine the relationship between work-life balance and job satisfaction and to analyze a relationship between work stress and job satisfaction.